Assessment of Myocardial Contractility by SonR Sensor in Patients Undergoing Cardiac Resynchronization Therapy. Issue 3 (12th January 2016) - SACCHI, STEFANIA; PERINI, ALESSANDRO PAOLETTI; ATTANÀ, PAOLA; GRIFONI, GINO; CHIOSTRI, MARCO; RICCIARDI, GIUSEPPE; PIERAGNOLI, PAOLO; PADELETTI, LUIGI
Abstract : Background: SonR sensor signal correlates well with myocardial contractility expressed in terms of left ventricular (LV) dP/dt max. The aim of our study was to evaluate the changes in myocardial contractility during isometric effort in heart failure patients undergoing cardiac resynchronization therapy (CRT) with right atrial SonR sensor. Methods: Thirty‐one patients (19 men, 65 ± 7 years, LV ejection fraction [LVEF] 28% ± 5%, in sinus rhythm) were implanted with a CRT‐defibrillator (CRT‐D) device equipped with SonR sensor, which was programmed in VVI mode at 40 beats/min. Twenty‐four hours after implantation, each patient underwent a noninvasive hemodynamic evaluation at rest and during isometric effort, including: (1) measurement of beat‐to‐beat endocavitary SonR signal; (2) echocardiographic assessment; and (3) continuous measurement of blood pressure with Nexfin method (BMEYE, Amsterdam, the Netherlands). The following contractility parameters were considered: (1) mean value of beat‐to‐beat SonR signal; (2) mean value of LV dP/dt by Nexfin system; and (3) fractional shortening (FS) by echocardiography. Results: At the third minute of the isometric effort, mean value of SonR signal significantly increased from baseline (P < 0.001). Similarly, mean value of both LV dP/dt by Nexfin and FS significantly increased compared to the resting condition (P < 0.001; P < 0.001). While in 27 (88%) patients SonR signal increased at the third minute of the isometric effort, in four (12%) patients SonR signal decreased. In these patients, both LV dP/dt by Nexfin and FS consensually decreased. Conclusions: In CRT patients, SonR sensor is able to detect changes in myocardial contractility in a consensual way like noninvasive methods such as Nexfin system and echocardiography.